Effectiveness of the pericardium (PC) 6 point massage on emesic decrease first trimester pregnant women - Yuliasti Eka Purnamaningrum; Yuni Kusmiyati; Iphigienia Iradati (PUINOVAKESMAS, 2021)
Hyperemesis gravidarum is a determinant of LBW occurrence of 4,821. The prevalence of emesis gravidarum is more than 80% of pregnant women in Indonesia. Nausea and vomiting can be treated non-pharmacologically. Determine the effectiveness of the Pericardium (PC) 6-point massage on the reduction of emesis in the first trimester of pregnant women. This study was quantitative research, experimental design approach with two-group design with pre posttest design. The population of pregnant women in the first trimester is 49. The sample in this study was 34 respondents who were pregnant in the first trimester using a randomization control trial technique. The PC6 group was given 2x massages at the pericardium 6 points for 1-3 minutes and the ginger group was given 2.5 g of ginger drink with 250 ml hot water, drunk 2x1 for 7 days. Data analysis used the Shapiro-Wilk test, the number of ratings obtained normal results data processing with paired T-test. That was mean decrease was 3.706 in the PC6 massage, while the mean decrease was 0.882 in the ginger. There was a difference in the decrease in emesis frequency in the calculation of the difference between the experimental group and the control group (p-value = 0.000 <0.005). There is the effectiveness of the Pericardium Point (PC) 6 massage on the reduction of emesis in first-trimester pregnant women.